Design And Simulation Of Low Noise Amplifier At 28 Ghz For 5g Wireless System - Yusof, Nur Syahadah (Universiti Sains Malaysia, 2017)
A tremendous growth in the mobile communication industry has increased the necessity for higher capacity and faster speed in wireless networks. The current speed of 4G LTE is about 20 Mbps to 1 Gbps. 5G technology is expected to have speed tenth times faster than 4G LTE could ever offer. The frequency spectrum allocated for current technology called as the fourth generation (4G) LTE wireless system is now overcrowded. Hence, a new frequency band is needed to support the future communication technology, which is known as the fifth generation (5G) wireless system. Ka-band is the prime candidate to be used in 5G technology. In order to manifest the idea behind 5G technology, a new transceiver system is needed. A transceiver system consists of a receiver and a transmitter network. Low Noise Amplifier (LNA) is an electronic component which is found at the front-end of receiver network. In this project, an LNA is designed to meet the 5G system requirements. The LNA is designed in Agilent Advanced Design System (ADS) software. A GaAs-based transistor, FHR02X working at 28 GHz from Fujitsu is used in the simulation as its characteristics is more likely the same as the transistor used in LNA fabrication process. An off-the-shelf GaAs pHEMT MMIC LNA HMC519LC4 from Hittite Corporation is used in layout and fabrication processes. The proposed design is then fabricated on the Rogers RO4003C board. The power gain of the LNA is measured by using a signal generator, together with a signal analyser. The input return loss